Penerapan Pemeriksaan Khusus Terhadap Piutang Pada PT Royal Bersaudara Di Balikpapan - Haolia, Putri Hajrina; Bone, Hamid; Utomo, Raden Priyo (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
The purpose of this research is to find out whether the PT Royal Bersaudara have presented accounts receivable in the financial statements that ended December 31, 2017 fairly. The analytical tool used in this assessment is the Entity Financial Accounting Standards without Public Accountability (SAK TAP) Chapter 4 About the balance sheet, inspection work papers consisting of the Accounts Receivable Audit Program, summary of the Adjudication journal and the Top Schedule and Supporting Schedule. The type of data used is quantitative data while the data source used is primary data. After checking the accounts receivable in the financial statements of PT Royal Bersaudara for the period 31 December 2017 found that no calculation and recording of losses on receivables was carried out on the balance sheet of PT Royal Bersaudara, so that the calculation of the receivables loss reserves resulting from Rp 202,497,781, then made adjustments by adding reserves of losses on accounts receivable in the balance sheet and reducing the profit for the year amounting to Rp 2,138,114,168